2012
DOI: 10.4084/mjhid.2012.070
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications in Chronic Lymphocytic Leukemia

Abstract: Infectious complications have been known to be a major cause of morbidity and mortality in Chronic Lymphocytic Leukemia (CLL) patients who are prone to infections because of both the humoral immunodepression inherent to the hematologic disease and to the immunosuppression related to the therapy. The majority of infections in CLL patients treated with alkilating agents is of bacterial origin. The immunodeficiency and natural infectious history of alkylator-resistant, corticosteroid-treated patients appears to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 70 publications
1
45
0
4
Order By: Relevance
“…Najczęstszymi powikłaniami obserwowanymi u pacjentów z CLL są nawracające, ciężkie zakażenia, które stanowią główną przyczynę zgonów, dotykającą nawet 30-50% pacjentów [1]. Przed wprowadzeniem terapii z użyciem analogów puryn u pacjentów z CLL leczonych środkami alkilującymi głównymi patogenami wywołują-cymi zakażenia były bakterie [2]. W chwili obecnej, ze względu na powszechne stosowanie immunochemioterapii w połączeniu z glikokortykosteroidami, obserwuje się nawracające, liczne, ciężkie, atypowe zakażenia wywołane nie tylko przez bakterie, ale także przez wirusy i grzyby [2].…”
unclassified
See 2 more Smart Citations
“…Najczęstszymi powikłaniami obserwowanymi u pacjentów z CLL są nawracające, ciężkie zakażenia, które stanowią główną przyczynę zgonów, dotykającą nawet 30-50% pacjentów [1]. Przed wprowadzeniem terapii z użyciem analogów puryn u pacjentów z CLL leczonych środkami alkilującymi głównymi patogenami wywołują-cymi zakażenia były bakterie [2]. W chwili obecnej, ze względu na powszechne stosowanie immunochemioterapii w połączeniu z glikokortykosteroidami, obserwuje się nawracające, liczne, ciężkie, atypowe zakażenia wywołane nie tylko przez bakterie, ale także przez wirusy i grzyby [2].…”
unclassified
“…Przed wprowadzeniem terapii z użyciem analogów puryn u pacjentów z CLL leczonych środkami alkilującymi głównymi patogenami wywołują-cymi zakażenia były bakterie [2]. W chwili obecnej, ze względu na powszechne stosowanie immunochemioterapii w połączeniu z glikokortykosteroidami, obserwuje się nawracające, liczne, ciężkie, atypowe zakażenia wywołane nie tylko przez bakterie, ale także przez wirusy i grzyby [2]. Jednym z oczywistych powodów zwiększonego ryzyka rozwoju zakażeń są zaburzenia odporności humoralnej.…”
unclassified
See 1 more Smart Citation
“…Defects in immune function related to CLL as well as related to treatment modality, predispose patients with CLL to a host of infections 3. The author reports a case of disseminated histoplasmosis mimicking relapsed disease in a patient treated for CLL.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent infections with encapsulated bacteria are common in both untreated as well as treated CLL, Staphylococcus aureus and various gram-negative enteric pathogens predominate during periods of neutropenia, while Herpes simplex and Varicella-zoster infections are associated with prior nucleoside analogue treatment. Fungal infections are encountered less often [7]. In a pooled analysis of clinical trials evaluating ibrutinib, grade 3-4 infections were reported in 14% of patients resulting in death in 2% [8].…”
Section: Introductionmentioning
confidence: 99%